Pengaruh Satisfaction, Loyalty dan Trust Terhadap WOM Behaviour pada Pelanggan Carrefour Lebak Bulus, Jakarta - Fitriani Fitriani; Vita Briliana (Jurnal Wira Ekonomi Mikroskil, 2018)
The purpose of this study is to know the influence of satisfaction, loyalty, and trust toward wom behavior of customers Carrefour Lebak Bulus, Jakarta. The data were collected using accidental sampling and used 105 respondents. The research data is processed with IBM statistic 19 as a tool. The results of this research has shown that loyalty and trust have influence to the wom behavior. While satisfaction have not influence to the wom behavior.